Analisis Yuridis Pertanggungjawaban Tindak Pidana Pencucian Uang Melalui Aset Kripto Di Indonesia - Bayu Pratama Yuda; Yoserwan Yoserwan; Riki Afrizal (Lareh Law Review, 2023)
Both Indonesia and countries that guide the establishment of crypto asset regulations such as America, Singgapura, and Japan, also face challenges related to their aspects and systems. With these aspects and systems, it will continue to complicate criminal liability for perpetrators who commit laundering. Theissues raised are; 1. How is the regulation regarding Money Laundering Crimes committed through Crypto Assets in Indonesian criminal law, 2. How is the Responsibility for Money Laundering Crimes committed through Crypto Assets. The research method used is normative juridical by examining from the point of view in the form of aspects of legality and criminal responsibility for perpetrators of money laundering through crypto assets based on Indonesian positive law. The results of the research obtained are; 1. The existing regulations in Indonesia currently relating to crypto assets, none of which include criminal provisions for perpetrators who use crypto assets as a mode of committing criminal acts. However, provisions in Law No. 11 of 2008 concerning Electronic Information and Transactions can be imposed on actors who use crypto assets as a new medium in committing criminal acts. And the use of crypto assets can also be classified as a mode of committing money laundering crimes, provided that the money converted into crypto assets comes from the proceeds of criminal acts as stated in article 2 of Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering. 2. Criminal liability for perpetrators who misuse crypto assets as a mode of committing money laundering can be subject to articles 3, 4, and 5 of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering. This is based on the normative error theory, the principle of strict liability and based on the judge's consideration in the decision of case No. 1240/Pid.Sus/2022/PN.Tng